Keeping It Clean: The Cell Culture Quality Control Experience at the National Center for Advancing Translational Sciences. (June 2020) - Roth, Jacob S.; Lee, Tobie D.; Cheff, Dorian M.; Gosztyla, Maya L.; Asawa, Rosita R.; Danchik, Carina; Michael, Sam; Simeonov, Anton; Klumpp-Thomas, Carleen; Wilson, Kelli M.; Hall, Matthew D.
Quality control monitoring of cell lines utilized in biomedical research is of utmost importance and is critical for the reproducibility of data. Two key pitfalls in tissue culture are 1) cell line authenticity and 2) Mycoplasma contamination. As a collaborative research institute, the National Center for Advancing Translational Sciences (NCATS) receives cell lines from a range of commercial and academic sources, which are adapted for high-throughput screening. Here, we describe the implementation of routine NCATS-wide Mycoplasma testing and short tandem repeat (STR) testing for cell lines. Initial testing identified a >10% Mycoplasma contamination rate. While the implementation of systematic testing has not fully suppressed Mycoplasma contamination rates, clearly defined protocols that include the immediate destruction of contaminated cell lines wherever possible has enabled rapid intervention and removal of compromised cell lines. Data for >2000 cell line samples tested over 3 years, and case studies are provided. STR testing of 186 cell lines with established STR profiles revealed only five misidentified cell lines, all of which were received from external labs. The data collected over the 3 years since implementation of this systematic testing demonstrate the importance of continual vigilance for rapid identification of "problem" cell lines, for ensuring reproducible data in translational science research.